2017
DOI: 10.1038/s41393-017-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Bedside quantification of fat-free mass in acute spinal cord injury using bioelectrical impedance analysis: a psychometric study

Abstract: The present study was funded by a grant from the Institute for Safety, Compensation and Recovery Research (ISCRR Project #NGE-E-13-078). M Panisset was supported by an Australian Postgraduate Award. K Desneves was supported by the Austin Medical Research Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…As detailed in Table 2 , a total number of 1,154 participants were included across the 42 articles, comprised of men (n = 1011) and women (n = 143) aged 16 to 71 years with cervical, thoracic or lumber lesion levels (C1 to L5), complete or incomplete SCI (American Spinal Injury Association Impairment Scale [AIS] A, B, C and D), mostly with a relatively long-standing SCI (all studies included participants ranging from 1 to 36 years post-injury [‘chronic’ SCI], except for three studies [ 38 , 56 , 60 ] including participants ranging from 3 days to 4 months post-injury [‘acute’ SCI]). All studies included SCI-only samples, except for one study that included a sample of at least 50% people with SCI mixed with participants with spinal bifida [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in Table 2 , a total number of 1,154 participants were included across the 42 articles, comprised of men (n = 1011) and women (n = 143) aged 16 to 71 years with cervical, thoracic or lumber lesion levels (C1 to L5), complete or incomplete SCI (American Spinal Injury Association Impairment Scale [AIS] A, B, C and D), mostly with a relatively long-standing SCI (all studies included participants ranging from 1 to 36 years post-injury [‘chronic’ SCI], except for three studies [ 38 , 56 , 60 ] including participants ranging from 3 days to 4 months post-injury [‘acute’ SCI]). All studies included SCI-only samples, except for one study that included a sample of at least 50% people with SCI mixed with participants with spinal bifida [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A two-compartment model of whole-body composition (total body electrical conductivity) in which participants were positioned in a whole-body cylinder was assessed for its test-retest reliability and was found to be acceptable (55). While no validity studies are available for this conductance method, seven other studies have assessed convergent validity of BIA compared to DXA [ 34 , 41 , 54 , 62 ] or total body water [ 32 , 38 , 56 , 62 ]; the majority were found to be inconclusive or not acceptable. Another two-compartment model of whole-body composition (skinfold thickness) showed acceptable test-retest reliability [ 33 ], however only three of the eight studies assessing whole-body convergent validity of skinfold thicknesses were acceptable when compared to DXA [ 41 , 49 , 54 , 62 , 69 ], total body water (38, 62), conductance [ 55 , 62 ], or hydrostatic weighing [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…FFM derived from BIS or DLW can be used in this equation. BIS may be the more practical alternative owing to its simplicity of use and lower cost [32]. Identification of hypermetabolism is important in order to individualise stress factors and could be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…FFM DLW and FM DLW were calculated from TBW derived from deuterium elimination rates by assuming a hydration fraction for FFM of 0.732 [31]. FM BIA was also predicted from whole body impedance measurements as described previously [32] using the prediction equation of Kocina and Heyward [33]. Fat mass predicted from impedance measurements (FM BIA ) was calculated as the difference between body weight and FFM BIA .…”
Section: Body Compositionmentioning
confidence: 99%
“…Reproducibility of the measurement was found to be worsened in individuals with higher body fat or lower muscle mass [35], which are prevalent in those with SCI. In addition, Panisset et al [36] reported that DEXA could underestimate muscle mass in individuals with acute SCI. To improve the accuracy of DEXA measurements, participants who were very obese or lean (BMI>30 or <15 kg/m 2 , respectively) were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%